Titrating Gene Function in the Human Fungal Pathogen Candida albicans through Poly-Adenosine Tract Insertion - Helene Tournu (American Society for Microbiology, 2019)
ABSTRACT A recent study demonstrated that the insertion of poly-adenosine (poly-A) tracts into an open reading frame can suppress expression of the encoded protein in both prokaryotic and eukaryotic species. Furthermore, the degree of suppression is proportional to the length of the poly-A insertion, which can therefore provide a reliable and predictable means to titrate a specific protein’s expression. The goal of this study was to determine if this methodology can be applied to modulate the expression of proteins in the prevalent human fungal pathogen, Candida albicans. Insertion of increasing numbers of AAA codons encoding lysine at the N terminus of the C. albicans lanosterol demethylase (Erg11p) progressively diminished expression without significantly reducing the levels of mRNA. This suggests that Erg11p expression was attenuated at the posttranscriptional level. A direct correlation between the number of AAA codons inserted and C. albicans susceptibility to the Erg11p inhibitor fluconazole was also noted, indicating a progressive loss of Erg11p activity. Finally, we constructed a series of C. albicans strains with 3 to 12 AAA codons inserted at the 5′ end of the ARO1 gene, which encodes a pentafunctional enzyme catalyzing five sequential steps of the aromatic amino acid biosynthetic pathway. Increasing numbers of AAA codons progressively reduced the growth rate of C. albicans in standard laboratory medium, indicating a progressive loss of ARO biosynthetic activity. These data unequivocally demonstrate the potential utility of the poly-A insertion method to examine the phenotypic consequences of titrating target protein function in C. albicans. IMPORTANCE Investigating a protein’s functional importance at the whole-organism level usually involves altering its expression level or its specific activity and observing the consequences with respect to physiology or phenotype. Several approaches designed to partially or completely abolish the function of a gene, including its deletion from the genome and the use of systems that facilitate conditional expression, have been widely applied. However, each has significant limitations that are especially problematic in pathogenic microbes when it is desirable to determine if a particular gene is required for infection in an animal model. In this study, we sought to determine if an alternative approach—the insertion of poly-A repeats within the coding sequence of the gene—is sufficient to modulate its function in the prevalent human fungal pathogen C. albicans. Our results confirm that this approach enables us to predictably and gradually titrate the expression level of a protein and thus to investigate the phenotypic consequences of various levels of gene/protein function.